Peranan Kepemilikan Manajerial sebagai pemoderasi Risk Investment Dan Kebijakan Utang Terhadap Nilai Perusahaan - Sundari, Febrina; Sugiyanto, Sugiyanto (Peneliti.net, 2023)
This study aims to analyze the determinants of firm value, both from investment risk and debt policy. Also from Managerial Ownership factor as a moderating variable. The method used is a quantitative method using secondary data. The population in this study are banks listed on the Indonesia Stock Exchange in 2018 - 2022. The sample used in this study totaled 9 banks with a 5-year observation period in the 2018 - 2022 period and the number of financial reports sampled in this study totaled 45 The analysis used is descriptive statistical analysis and multiple regression analysis. The analytical tool used in this study is analysis with the help of the E-views Version 12 program. The results of the research conducted show that Simultaneous Risk Investment and Debt Policy have a significant influence on Company Value. While Partially Risk Investment Has No Effect on Firm Value, Debt Policy partially Affects Company Value. The results of the Managerial Ownership variable test strengthen the relationship between Risk Investment and Firm Value and the results of the Managerial Ownership variable test do not strengthen the relationship between Debt Policy and Company Value.